Departamento de Odontologia Restauradora - Briso, André Luiz Fraga; Cintra, Luciano Tavares Angelo; Dezan Júnior, Eloi; Sundfeld, Renato Herman; Shinohara, Mirela Sanae; Mestrener, Sandra Rahal; Bernabé, Pedro Felício Estrada; Nery, Mauro Juvenal; Otoboni, José Arlindo; Gomes Filho, João Eduardo; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - André Luiz Fraga Briso